Restoration of Hatirjheel Lake by designing submerged aeration system and settling zone. Issue 1 (April 2020) - Anber, Fabliha; Iqra, Nazeat Ameen; Badruzzaman, A.B.M.
Abstract: Hatirjheel Lake is known as the centre of the Dhaka city, the capital of the Bangladesh, a South Asian riverine country. But, unfortunately, soon this lake will be darken due to huge pollution. Therefore, to augment dissolve oxygen level, aeration system has been acknowledged as an effective way for the lake restoration, and an aeration zone and for further improvement settling zone have been designed. First of all, our study is assessed bifurcating the total area into two segments: aeration zone and sedimentation zone. Total oxygen requirement and other fundamental tests have been derived from sample. Later, to meet 83mg/l of oxygen demand number of diffusers of 8in diameter have been enumerated, and additionally three root lobe blowers of a centrifugal pump are selected, and desludging time interval has been computed. Conclusively, the percentage removal of particles has been substantialized through laboratory-based batch column. In our study, we have considered maximum discharge of 6 ft 3 /s whilst even during the rainy season more than 50% incoming water will be transferred via twin diversion sewers. Therefore, we can say our design is in the satisfactory zone.